(3cJGH GdJLQjOs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3eMeO Hf CHj GdWjH s)
(3ChdgG (B:s
(3fMeO Gddg MeO GdTGcQjf hHYO aEfG CQOfG Cf fLQO CUhd GdefWb heGFdg Ydi GdJQJjH GdaUd GdChd ai eONd gPG GdYde GddaX jOd Ydi JeGe eYfGg s
(3BNQgG (B:s
(3dCfgG cdeG cGJ CZQH agi CdP hCYLH Je cJGH GdJLQjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B351s
Keywords: (3GdadSaI hGdefWbs